Carina's defiant finger: HST observations of a photoevaporating globule in NGC 3372 - Smith, Nathan (2004)
We present Hubble Space Telescope Wide Field Planetary Camera 2 images of a prominent externally ionized molecular globule in the Carina Nebula (NGC 3372), supplemented with ground-based infrared images and visual-wavelength spectra. This molecular globule has a shape resembling a human hand, with an extended finger that points toward its likely source of ionizing radiation. Following an analysis of the spatially resolved ionization structure and spectrum of the photoevaporative flow from the Finger, we conclude that the dominant ionizing source is either the WNL star WR25 (HD 93162), the adjacent O4 If-type star Trl6-244, or perhaps both. We estimate a mass-loss rate of ∼2 × 10-5 M⊙ yr-1 from the main evaporating surface of the globule, suggesting a remaining lifetime of 10 5.3-106 yr. We find a total mass for the entire globule of more than 6 M⊙ , in agreement with previous estimates. The hydrogen column density through the globule derived from extinction measurements is a few times 1022 cm-2, so the photodissociation region behind the ionization front should be limited to a thin layer compared to the size of the globule, in agreement with the morphology seen in H2 images. Although a few reddened stars are seen within the boundary of the globule in near-infrared continuum images, these may be background stars. We do not detect a reddened star at the apex of the finger, for example, down to a limiting magnitude of mk≃ 17. However, considering the physical properties of the globule and the advancing ionization front, it appears that future star formation is likely in the Finger globule, induced by radiation-driven implosion.